2010
DOI: 10.1056/nejmoa0808836
|View full text |Cite
|
Sign up to set email alerts
|

Percent Emphysema, Airflow Obstruction, and Impaired Left Ventricular Filling

Abstract: BACKGROUND Very severe chronic obstructive pulmonary disease causes cor pulmonale with elevated pulmonary vascular resistance and secondary reductions in left ventricular filling, stroke volume, and cardiac output. We hypothesized that emphysema, as detected on computed tomography (CT), and airflow obstruction are inversely related to left ventricular end-diastolic volume, stroke volume, and cardiac output among persons without very severe lung disease. METHODS We measured left ventricular structure and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
384
3
26

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 498 publications
(446 citation statements)
references
References 53 publications
33
384
3
26
Order By: Relevance
“…We have recently shown that former and current smokers are at increased risk of elevated heart rate compared to never-smokers [7]. These findings are in line with BARR et al [25] who found a significant interaction between smoking status and stroke volume in subjects with pulmonary dysfunction; smokers were found to have lower ventricular dimensions compared to Risk reclassification: forced expiratory volume in 1 s (FEV1) % predicted versus FEV1 % pred with resting heart rate. Resting heart rate improves the risk prediction when added to a model with FEV1 % pred alone.…”
Section: Copd | Mt Jensen Et Alsupporting
confidence: 88%
See 1 more Smart Citation
“…We have recently shown that former and current smokers are at increased risk of elevated heart rate compared to never-smokers [7]. These findings are in line with BARR et al [25] who found a significant interaction between smoking status and stroke volume in subjects with pulmonary dysfunction; smokers were found to have lower ventricular dimensions compared to Risk reclassification: forced expiratory volume in 1 s (FEV1) % predicted versus FEV1 % pred with resting heart rate. Resting heart rate improves the risk prediction when added to a model with FEV1 % pred alone.…”
Section: Copd | Mt Jensen Et Alsupporting
confidence: 88%
“…Low arterial oxygen saturation leads to an increase in cardiac output [24]. Furthermore, pulmonary dysfunction in COPD is associated with an incremental decrease in left ventricular size and stroke volume [25,26]. When stroke volume is decreased, cardiac output can be maintained by an increase in heart rate.…”
Section: Copd | Mt Jensen Et Almentioning
confidence: 99%
“…Recently, Barr and colleagues have shown that CT-quantified emphysema scores negatively correlated with ventricular filling even in a group without COPD and minor emphysema where hyperinflation is unlikely to play a role [47]. They hypothesize that endothelial dysfunction associated with emphysema leads to impaired left ventricular filling.…”
Section: Heart Failure Secondary To Impaired Fillingmentioning
confidence: 99%
“…COPD is both a premorbid identifier of HFpEF [75] and a contributor to HFpEF mortality [21]. In a population-based study, greater severity of COPD was linearly related to impaired LV filling, reduced stroke volume and lower cardiac output without changes in EF [76]. Anemia is more prevalent in HFpEF than in HFrEF patients [77] and associated with increased risk of HF hospitalization [78] and overall mortality [79].…”
Section: Copd Anemia and Renal Failurementioning
confidence: 99%